Association between Loa loa microfilaremia and anatomical hyposplenia in a rural area of the Republic of Congo: a population-based cross-sectional study - Charlotte Boullé; Elodie Lebredonchel; Jérémy T. Campillo; Valentin Dupasquier; Marlhand C. Hemilembolo; Sébastien D. S. Pion; Jean Claude Djontu; Ludovic Rancé; Philippe Souteyrand; François Missamou; Michel Boussinesq; Francine Ntoumi; et al. (Infectious Diseases of Poverty)
Abstract Background Data suggest excess mortality is associated with loiasis, which is endemic to Central Africa, although the underlying mechanisms remain unknown. We hypothesized that there could be an association between Loa loa microfilarial densities (MFD) and lower spleen volume (SV) due to micro-obstruction linked to circulating microfilariae (mf). This could result in functional hyposplenia and a higher burden of infections. Our objective was to investigate the impact of L. loa MFD and malaria on spleen’s bi-dimensional dimensions, volume, and parenchymal lesions. Methods We included 981 participants aged 18–88 years in a cross-sectional study conducted in May–June 2022 in the Republic of the Congo. Centralized ultrasonographic examination was performed. The primary outcomes included SV, splenomegaly (cranio-caudal-distance ≥ 13 cm), and anatomical hyposplenia (AH) (SV ≤ 80, ≤ 110 or ≤ 150 cm3). Blood samples were analyzed for L. loa MFD, Plasmodium-PCR, Anti-Plasmodium falciparum-IgG, total IgM, sickle-cell disease status, and hematological abnormalities. Linear and logistic regressions were used to assess these associations. Results Among 981 participants, 139 (14.1%) had splenomegaly, and 26 (2.7%) and 175 (17.8%) had SV ≤ 80 and ≤ 150 cm3, respectively. L. loa microfilariae were detected in 353 (35.6%) participants. A gradient effect was observed in each model, with the highest MFD (> 30,000 mf/ml) having the highest adjusted odds ratio of 17.94 (95% CI: 2.91–110.76, P = 0.002), 5.94 (95% CI: 1.40–25.17, P = 0.016), and 5.77 (95% CI: 1.95–17.12, P = 0.002) for SV ≤ 80, 110, and 150 cm3, respectively. Anti-P. falciparum-IgG levels were gradually associated with splenomegaly. Fourteen participants met the criterion for hyper-reactive malarial splenomegaly (HMS). Conversely, higher L. loa MFD was correlated with AH, with an attributable fraction of 25%, and the presence of splenic parenchymal lesions. Conclusions This study provides a detailed description of spleen morphology and the factors influencing its size in a rural central African population. It demonstrates a strong association between L. loa MFD and reduced SV, suggesting that loiasis may lead to AH, and potentially to functional hyposplenia, with consequences such as increased susceptibility to bacterial infections. Malaria was associated with splenomegaly, with a figure of HMS consistent with estimates from other African countries. Graphical Abstract